DIPLOMASI PENDIDIKAN INDONESIA DI WILAYAH THAILAND SELATAN PASCA COVID-19 - Khunaivi, Aldi Syahrul; Pahlawan, Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This research analyzes Indonesia's efforts to carry out educational diplomacy in the Southern Thailand region after the Covid-19 pandemic within the scope of 2022 until 2023. Covid-19 has caused delays in several cooperation programs carried out by the Indonesian Government through the Consulate of the Republic of Indonesia (KRI) in Songkhla as Indonesian representative. Educational cooperation programs carried out by Indonesia and Southern Thailand, such as scholarships, student exchanges, and others, experienced setbacks during the pandemic. In 2022, KRI Songkhla will again make efforts to improve educational cooperation programs through several programs such as reopening scholarships, teaching programs, outreach and activities that support the re-creation of good cooperation. This research uses qualitative methods, with data collection techniques through literature studies sourced from several annual reports, journals, articles and websites. This research use the diplomacyn theory. The results of this research show the effects of the improvement efforts made by KRI Songkhla in educational cooperation in the Southern Thailand region, such as the reopening of the Indonesian Arts and Culture Scholarship which welcomed back 8 (eight) Southern Thai students and the re-introduction of face-to-face teaching programs. Key Words : Billateral Relation, KRI Songkhla, Covid-19, Education